PRKRA promotes pancreatic cancer progression by upregulating MMP1 transcription via the NF-κB pathway - Jiangdong Qiu; Mengyu Feng; Gang Yang; Dan Su; Fangyu Zhao; Yueze Liu; Jinxin Tao; Wenhao Luo; Taiping Zhang (Heliyon, 2023)
Objective: Pancreatic cancer (PC) is highly malignant, but the underlying mechanisms of cancer progression remain unclear. PRKRA is involved in cellular stress response, but its role in PC was unknown. Methods: The expression of PRKRA between normal and tumor tissues were compared, and the prognostic value of PRKRA was evaluated. SiRNA and plasmids were applied to investigate the effects of PRKRA on PC cells. Organoids and cell lines with knockout and overexpression of PRKRA were established by CRISPR/Cas9 and lentivirus. The effects of PRKRA on PC were evaluated in vivo by cell-derived xenografts. The downstream genes of PRKRA were screened by transcriptome sequencing. The regulation of the target gene was validated by RT-qPCR, western blot, ChIP and dual luciferase reporter assay. Besides, the correlation between PRKRA and gemcitabine sensitivity was investigated by PC organoids. Results: PRKRA was significantly overexpressed in PC tissues and independently associated with poor prognosis. PRKRA promoted the proliferation, migration, and chemoresistance of PC cells. The proliferation of PC organoids was decreased by PRKRA knockout. The growth and chemoresistance of xenografts were increased by PRKRA overexpression. Mechanistically, PRKRA upregulated the transcription of MMP1 via NF-κB pathway. ChIP and dual luciferase reporter assay showed that NF-κB subunit P65 could bind to the promoter of MMP1. The sensitivity of PC organoids to gemcitabine was negatively correlated with the expression of PRKRA and MMP1. Conclusions: Our study indicated that the PRKRA/NF-κB/MMP1 axis promoted the progression of PC and may serve as a potential therapeutic target and prognosis marker.